2012
DOI: 10.4111/kju.2012.53.11.779
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Enucleation of the Prostate: Modified Morcellation Technique and Results

Abstract: PurposeWe developed an inverse technique for tissue morcellation by modifying the conventional upward technique and then examined its safety and efficiency.Materials and MethodsFrom July 2008 to December 2010, a total of 389 consecutive patients treated with holmium laser enucleation of the prostate (HoLEP) were enrolled in this study. For tissue morcellation, we used an upward technique for an initial series of 84 patients and an inverse technique for a consecutive series of 305 patients. We compared efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For this reason, we could not detect a relationship between bladder mucosal injury and postoperative continence acquisition. This is likely due to the adoption of morcellator surgery via the inverse technique [24,28,29], which is associated with fewer complications. Even after considering the operator influence in one of sub-analyses, the UI status immediately after surgery was shown to be a good predictor of postoperative continence acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we could not detect a relationship between bladder mucosal injury and postoperative continence acquisition. This is likely due to the adoption of morcellator surgery via the inverse technique [24,28,29], which is associated with fewer complications. Even after considering the operator influence in one of sub-analyses, the UI status immediately after surgery was shown to be a good predictor of postoperative continence acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…A modification of the technique to increase morcellation efficiency and to lessen the incidence of bladder injury is called "the inverse technique." 27 It entails sucking the adenoma toward the blades then inversely rotating the nephroscope and the blades, with the blade openings pointing inferior toward the bladder and superior to the prostate tissue. Lee and colleagues reported a higher rate of tissue retrieval with their technique using the VersaCut morcellator.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 12) reported that an inverse morcellation technique was safer and more efficient than the existing upward technique. This technique removes the glade between the blade and bladder wall with suction by placing the blade in the inverse position.…”
Section: Discussionmentioning
confidence: 99%